(untitled) (Bangladesh Journal of Agricultural Research, 2013)
An investigation was undertaken to study the feasibility of sugarbeet cultivation under Bangladesh condition during winter season of 2009-2010. Seeds of 14 sugarbeet genotypes were sown in the experimental field of Horticulture Research Centre of BARI, Gazipur on 10 November 2009. Visible root swelling in all genotypes started between 36 and 40 days after sowing (DAS). Nine genotypes had white root colour while rest were red purple. Plant height varied from 26.8 cm to 55.0 cm at 165 DAS. Similarly, whole plant weight among the genotypes ranged from 0.76 kg to 1.60 kg. Mean root yield in all genotypes was 66.22 t/ha when harvested at 165 DAS, which was decreased to 56.29 t/ha at 180 DAS. However, the highest root yield was recorded from the genotypes SB001 (85.30 t/ha) closely followed by SB006 (84.40 t/ha) at 165 DAS. All the genotypes showed lower yield potential at 180 DAS compared to 165 DAS. Severe leaf shedding and drying up of the root in the later stage might be the reason for yield reduction. Nine genotypes had more than 10% sucrose and can be considered for sugar producing genotypes. Five genotypes had very less sucrose content in the root and can be useful for vegetable purpose. The genotypes SB001 and SB006 had comparatively high amount of sucrose (13.0%) in the root. The fungal disease Sclerotium root rot and the insect Spodoptera litura were found the most limiting factor for sugarbeet cultivation. DOI: http://dx.doi.org/10.3329/bjar.v37i4.14396 Bangladesh J. Agril. Res. 37(4): 721-728, December 2012